A new sensitizer containing dihexyloxy-substituted triphenylamine as donor and a binary conjugated spacer for dye-sensitized solar cells1. Issue 66 (19th July 2015) - Damaceanu, Mariana-Dana; Mihaila, Mihai; Constantin, Catalin-Paul; Chisca, Stefan; Serban, Bogdan-Catalin; Diaconu, Cristian; Buiu, Octavian; Pavelescu, Emil Mihai; Kusko, Mihaela
<x xml:space="preserve">Abstract</x> A new D–π–A dye based on dihexyloxy-substituted triphenylamine moiety has been synthesized and its preliminary performances in DSSCs are reported.